Occurrence of plant growth-promoting traits in clover-nodulating rhizobia strains isolated from different soils in Rio Grande do Sul state - Vargas,Luciano Kayser (2009)
In the last decades, the use of plant growth-promoting rhizobacteria has become an alternative to improve crop production. Rhizobium leguminosarum biovar trifolii is one of the most promising rhizobacteria and is even used with non-legume plants. This study investigated in vitro the occurrence of plant growth-promoting characteristics in several indigenous R. leguminosarum biovar trifolii isolated from soils in the State of Rio Grande do Sul, Brazil. Isolates were obtained at 11 locations and evaluated for indoleacetic acid and siderophore production and inorganic phosphate solubilization. Ten isolates were also molecularly characterized and tested for antagonism against a phytopathogenic fungus and for plant growth promotion of rice seedlings. Of a total of 252 isolates, 59 produced indoleacetic acid, 20 produced siderophores and 107 solubilized phosphate. Some degree of antagonism against Verticillium sp. was observed in all tested isolates, reducing mycelial growth in culture broth. Isolate AGR-3 stood out for increasing root length of rice seedlings, while isolate ELD-18, besides increasing root length in comparison to the uninoculated control, also increased the germination speed index, shoot length, and seedling dry weight. These results confirm the potential of some strains of R. leguminosarum biovar trifolii as plant growth-promoting rhizobacteria.